PENGARUH PENGGUNAAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN PEMAHAMAN MATEMATIKA SISWA SEKOLAH DASAR KELAS V - Taufiqulloh Dahlan; Rina Indriani; Acep Roni Hamdani; Sudewa Ridzki Darajat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by the lack of innovation in mathematics lessons with the use of learning models that cause students to lack understanding of mathematics and students' lack of response in paying attention as evidenced by the low level of student understanding in learning mathematics. The purpose of this study was to determine the effect and increase in understanding of mathematics learning between the control class which was given conventional learning treatment and the experimental class which was given the discovery learning model treatment on increasing elementary school students' understanding of mathematics. This research is a quasi-experimental research with the research design used is nonequivalent control group desgin. The samples in this study were fifth grade students of SD N 1 Langensari consisting of 2 classes, namely V A control class and V B experimental class with a total of 50 students. Data collection techniques in the study used tests and observations. The pretest and posttest tests given to the research sample classes were in the form of the same questions and comprehension observation sheets. After the test data was obtained, the researcher analyzed the data and showed that the average posttest in the experimental class was higher than the control class. In addition, the analysis was carried out with the Independent Sample Test test with the help of the SPSS 16 application, obtained the sig value. (2-tailed) of 0.000 <0.05. Ngain test was conducted, obtained an average value of 0.72> 0.7 has a high effect. So it can be concluded that the effect of the discovery learning model on mathematical understanding is higher than the conventional class.